Perencanaan Produk Paket Wisata Heritage di Paguyuban Pelestarian Budaya Bandung - Danudara, Ananta Budhi (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2017)
Paguyuban Pelestarian Budaya Bandung (Bandung Heritage) is a non profit organization moving to execute activity of conservation for physical heritage plant in Bandung. The activities of Bandung Heritage are inventorying historic landmark and cultural landscapes, acting as an advisory body to public and private sector organizations requiring specialist- conservation advice, held the exhibitions, performances and other artistic and cultural events; publishing books of heritage building in Bandung. There must be the other alternative way to support the conservation of heritage building in Bandung besides the. above things that Bandung Heritage did. The alternative way is to plan the heritage tour package in Bandung. The compilation of heritage tour package is based on the tour components such as attraction, facility and accessibility. The components were analyzed in order to become a competent supplementary factor for the activity of heritage tour in Bandung